Design And Development of A Monitoring And Prediction System For Sari Roti Returns In Aceh Utara Using The Single Exponential Smoothing Method - Farhan Kamil; Huzaeni Huzaeni; Amirullah Amirullah (Politeknik Negeri Lhokseumawe, 2026)
This research focuses on inventory management of Sari Roti branded bread products in North Aceh, Indonesia, which faces financial loss problems due to unexpected product returns. Currently, return calculations are done manually, but this method is still inadequate. This study aims to develop a bread inventory prediction system using the single exponential smoothing method. In this context, Sari Roti is a leading bread manufacturer with various types of bread products. The main problem is the difficulty in estimating the quantity of bread that will be returned by stores in the region. To improve inventory estimation accuracy, this research introduces a prediction and monitoring system that enables stores to track the amount of bread stock to be supplied and the quantity of returns by salespeople each week. The method used is Single Exponential Smoothing, which seeks to improve upon the previous method that had a high error rate. This research is expected to help sales personnel and Sari Roti distributors in North Aceh predict bread return quantities more accurately, with the goal of reducing financial losses due to unexpected returns. The use of the Single Exponential Smoothing method to predict returns and drops for the 10 most common Sari Roti products from each store in North Aceh with an alpha value of 0.3 is quite good, because the prediction results obtained using Mean Absolute Deviation (MAD) error evaluation yielded an average error value below 10%, while the prediction results obtained using Mean Absolute Percentage Error (MAPE) evaluation are not yet satisfactory, because the average error value obtained is below 40%.